Pemberdayaan Generasi Muda Melalui Program Lomba Muslim Berprestasi Di Desa Panjiwangi, Kabupaten Garut: Upaya Kkn Reguler Universitas Muhammadiyah Bandung Dalam Membangun Sebuah Karakter Dan Prestasi - Aliman Khoerul Ibad; Qisthina, Syamila Diena; Sapnah; Pahmi Sami Ali; Nazhif Almas Rizquloh; Septiawansyah, M. Rizki Putrangga; Dini Septiani; Diana Farid; Ayuri Nanda Mentari; Caesarina, Syifa Sauqinah Sestia (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
Religious education has an important role in building character and moral values of the younger generation, especially in the era of globalization. This research explores the implementation of Lomba Muslim Berprestasi (LMB) in Panjiwangi Village, Garut Regency, which aims to develop the potential of Madrasah Diniyah Takmiliyah (MDT) students in various fields, as well as strengthen Islamic values. Using a qualitative approach with a case study method, this research involved 52 participants from 8 Madrasah Diniyah Takmiliyah (MDT). The results showed that this activity succeeded in raising community awareness about Islamic character education and provided a fun learning experience for participants. The competition, which consisted of Musabaqah Hifdzil Qur'an (MHQ), Da'i Cilik (DACIL), Calligraphy, and Adhan, not only increased the participants' independence and confidence, but also motivated them to contribute positively to society. Therefore, the Muslim Achievement Competition (LMB) is an effective tool in producing a young generation of achievers and noble characters.